Wahana Edukasi Dan Kemandirian Pangan Dengan Biokonversi Sampah Organik Rumah Tangga - NUR Chabibah; Rini Kristiyanti; Anis Sofiana; Milatun Khanifah (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2019)
Waste is an environmental problem faced by all settlements. Waste management constraints such as the difficulty of land where the final processing, the limited fleet of transporters, the lack of public awareness to manage waste from the source, the technology of waste management is still traditional, to the constraints of the lack of human resources regarding waste management. In addition, waste management requires not a small amount of money. The community needs sufficient technology and information support to be able to participate in waste management. The purpose of this activity is to invite the community to process household organic waste so that it can lift economic value and food independence. The methods that were carried out included education of waste sorting, training on household organic waste processing techniques using the bioconversion method and utilization of waste management byproducts, making installations and operations for processing household organic waste, utilizing the by-products of processing household organic waste in the form of organic fertilizers and substitutes animal feed, evaluating the implementation of activities and making follow-up plans for environmental development and micro business development. The level of community service in the form of increasing knowledge of waste sorting and the skills of residents in utilizing household organic waste as well as the results of waste residues as organic fertilizer and animal feed ingredients so that it can help food independence at the household level.